Development of Traditional Sports Module Based on Project Based Learning for Students - Ali, Masnur; Nugraha, Hartman; Kholik, Abdul; Maslikah, Uzizatun (Department of Physical Education, Sport, Health and Recreation, 2023)
The purpose of this research is to produce a traditional sports learning module based on project based learning for students. The module aims to actively involve students in preserving traditional sports by analyzing a problem related to traditional sports and then conducting a structured project analysis to solve the problem. This research is a development research or Research & Development. The development procedure in the 4-D model involves four stages, namely definition, design, development, and dissemination. Based on the results of field needs analysis, which shows that a traditional sports learning module is highly needed for students to directly collaborate in preserving traditional sports. The subjects of this research are 40 recreational sports students. The results of the research show that the traditional sports learning module based on project based learning can improve students' skills in analyzing a problem, conducting a project to answer the problem, and in line with 21st-century learning 4C, which are critical thinking and problem solving, creativity, communication skills, and the ability to work collaboratively.